Correntes induzidas e condensado fermiônico no espaço-tempo de uma corda cósmica - Bragança, Eduardo André de Figueiredo (2017)
In this thesis, we investigate the e ect of the topology and the magnetic eld on the vacuum uctuations associated to bosonic and fermionic charged elds. Firstly, we analize the vacuum induced current densities for a bosonic eld in a (D+1)-dimensional cosmic string spacetime. For this analysis, we consider the presence of a magnetic eld along of the azimuthal and axial directions and that the z-axis is compacti ed to a circle of lenght L. This analysis is performed using the positive frequencies Wightman function, that is necessary to calculate the vacuum expectation values of the induced current densities. Our second investigation is related with fermionic elds. We investigate the expectation values of the fermionic condensate, h i, charge and current densities for a massive fermionic eld in thermal equilibrium with T temperature, with a nonzero chemical potential, . We consider the background of a (2+1)-dimensional conical spacetime and the presence of a magnetic eld in the cone apex. In this analysis, we consider two separeted cases. Firstly, we consider the case where j j 6 m and after that the case where j j > m.